2022
DOI: 10.3892/ol.2022.13547
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of polo‑like kinase 4 in renal cell carcinoma: Association with clinicopathological characteristics and long‑term survival

Abstract: Polo-like kinase 4 (PLK4) promotes tumorigenesis and is associated with the prognosis of several solid tumors, while its clinical role in patients with renal cell carcinoma (RCC) remains unidentified. The present study aimed to analyze the association of PLK4 with clinicopathological characteristics and long-term prognosis in patients with RCC. The present study detected PLK4 protein and mRNA expression using immunohistochemical and reverse transcription-quantitative PCR assays in 120 patients with RCC. Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For example, one study showed that increased PLK4 mRNA expression is linked with tumor stage in non-small cell lung cancer patients [ 17 ]. Another study indicated that increased PLK4 mRNA expression is associated with tumor size ≥ 7 cm and high tumor node metastasis (TNM) stage in renal cell carcinoma [ 18 ]. A study elucidated that PLK4 mRNA expression is linked with a higher incidence of lymph node metastasis and distant metastasis or surrounding recurrence in breast cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study showed that increased PLK4 mRNA expression is linked with tumor stage in non-small cell lung cancer patients [ 17 ]. Another study indicated that increased PLK4 mRNA expression is associated with tumor size ≥ 7 cm and high tumor node metastasis (TNM) stage in renal cell carcinoma [ 18 ]. A study elucidated that PLK4 mRNA expression is linked with a higher incidence of lymph node metastasis and distant metastasis or surrounding recurrence in breast cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the correlation of PLK4 with tumor features (Duan et al 2022, Jiang et al 2022, Jiawei et al 2022. For example, one study indicates that tumor PLK4 expression is associated with advanced TNM stage in colorectal cancer patients (Duan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study indicates that tumor PLK4 expression is associated with advanced TNM stage in colorectal cancer patients (Duan et al 2022). Another study elucidates that upregulation of PLK4 expression is linked with poor tumor differentiation and increased TNM stage in renal cell carcinoma patients (Jiang et al 2022). This study also found that elevated tumor PLK4 IHC score was correlated with lymph node metastasis, higher TNM stage, and adjuvant therapy in patients with cutaneous melanoma who underwent surgical resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations